Amniotic-Umbilical-to-Cerebral Ratio-A Novel Ratio Combining Doppler Parameters and Amniotic Fluid Volume to Predict Adverse Perinatal Outcome in SGA Fetuses at Term - Stumpfe, Florian; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Emons, Julius; Gaß, Paul; Mayr, Andreas; Schmid, Matthias; Beckmann, Matthias; Stelzl, Patrick (Ultraschall in der Medizin, 2020)
Purpose â Introduction of a novel ratio-the amniotic-umbilical-to-cerebral ratio (AUCR)-to predict adverse perinatal outcome in SGA fetuses at term and comparison of its predictive accuracy with established parameters. Materials and Methods â This retrospective cohort study included 165 singleton pregnancies with SGA fetuses (birth weight <âŠ10 thpercentile) at term. Cases with planned vaginal delivery and documented pulsatility indices (PI) of the umbilical artery (UA), middle cerebral artery (MCA), and single deepest pocket (SDP) were included. CPR was calculated as the ratio between MCA PI and UA PI, UCR as the ratio between UA PI and MCA PI. AUCR was defined as follows: SDP/(UA PI/MCA PI). Adverse perinatal outcomes were defined as operative intervention (OI), OI due to fetal distress, admission to the neonatal intensive care unit (NICU), and composite adverse perinatal outcome (CAPO). Associations between Doppler parameters and these outcomes were estimated using regression analyses. Results â OI was statistically significantly associated with UCR, SDP, and AUCR, whereas no association was observed for UA PI, MCA PI, and CPR. Fetuses requiring OI due to fetal distress revealed a significantly higher UA PI and UCR as well as a lower MCA PI, CPR, and AUCR. With regard to NICU admission and CAPO, a significantly higher UA PI and lower CPR were found. Furthermore, a significant association was shown for SDP, UCR, and AUCR. AUCR achieved the best area under the curve for all outcome parameters. Conclusion â AUCR leads to an improvement in the prediction of unfavorable outcome in SGA fetuses at term. Furthermore, results of our study show that UCR might be superior to CPR.
CRIS-Team Scopus Importer:2020-11-13
Keywords: amniotic fluid; AUCR; CPR; SDP; UCR

Correlation of short-term variation and Doppler parameters with adverse perinatal outcome in small-for-gestational age fetuses at term - Stumpfe, Florian M.; Faschingbauer, Florian; Kehl, Sven; Pretscher, Jutta; Stelzl, Patrick; Mayr, Andreas; Schild, Ralf L.; Schmid, Matthias; Beckmann, Matthias; Schneider, Michael (Archives of Gynecology and Obstetrics, 2019)
Objective: To evaluate the association of short-term variation (STV) and Doppler parameters with adverse perinatal outcome in small-for-gestational-age (SGA) fetuses at term. Methods: In this retrospective single-center study 97 patients with singleton SGA fetuses at term (≥ 37 + 0 weeks’ gestation) were examined. Inclusion criteria were a birth weight < 10th centile, cephalic presentation and planned vaginal birth. Only cases with available Doppler measurements of umbilical artery (UA) and middle cerebral artery (MCA) with calculated cerebroplacental ratio (CPR) in combination with a computerized CTG (cCTG) and STV 72 h prior to delivery were eligible for analysis. Pulsatility indices (PI) were converted into multiples of median (MoM), adjusted for gestational age. The association between Doppler indices and STV values with mode of delivery [secondary cesarean delivery (CD), operative vaginal delivery (OVD), as well as secondary CD and OVD due to fetal distress] and neonatal outcome [UA blood pH ≤ 7.15 and the need of admission to the neonatal intensive care unit (NICU)] was analyzed using logistic regression analysis. Results: There was a significant association between UA PI MoM and the rate of CD. CD due to fetal distress, OVD and OVD due to fetal distress did not show a correlation with the evaluated Doppler parameters. Furthermore, we did not find an association between low UA birth pH and Doppler parameters while neonates with the need of admission to NICU had significant higher UA PI MoM and significant lower MCA PI MoM and CPR MoM. Regarding STV, a significant effect of low STV on NICU admission was found while none of the other assessed outcome parameters were significantly associated with STV. Conclusion: STV and Doppler parameters in SGA fetuses at term are significantly associated to the rate of NICU admission.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Cardiotocography; Cerebroplacental ratio; Computerized CTG; Doppler; Fetal distress; SGA; Short-term variation; small-for-gestational age

HELLP Syndrome or Acute Fatty Liver of Pregnancy: A Differential Diagnostic Challenge - Rath, Werner; Tsikouras, Panagiotis; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2020)
HELLP syndrome and the less common acute fatty liver of pregnancy (AFL) are unpredictable, life-threatening complications of pregnancy. The similarities in their clinical and laboratory presentations are often challenging for the obstetrician when making a differential diagnosis. Both diseases are characterised by microvesicular steatosis of varying degrees of severity. A specific risk profile does not exist for either of the entities. Genetic defects in mitochondrial fatty acid oxidation and multiple pregnancy are considered to be common predisposing factors. The diagnosis of AFL is based on a combination of clinical symptoms and laboratory findings. The Swansea criteria have been proposed as a diagnostic tool for orientation. HELLP syndrome is a laboratory diagnosis based on the triad of haemolysis, elevated aminotransferase levels and a platelet count < 100 G/l. Generalised malaise, nausea, vomiting and abdominal pain are common symptoms of both diseases, making early diagnosis difficult. Clinical differences include a lack of polydipsia/polyuria in HELLP syndrome, while jaundice is more common and more pronounced in AFL, there is a lower incidence of hypertension and proteinuria, and patients with AFL may develop encephalopathy with rapid progression to acute liver failure. In contrast, neurological symptoms such as severe headache and visual disturbances are more prominent in patients with HELLP syndrome. In terms of laboratory findings, AFL can be differentiated from HELLP syndrome by the presence of leucocytosis, hypoglycaemia, more pronounced hyperbilirubinemia, an initial lack of haemolysis and thrombocytopenia < 100 G/l, as well as lower antithrombin levels < 65% and prolonged prothrombin times. While HELLP syndrome has a fluctuating clinical course with rapid exacerbation within hours or transient remissions, AFL rapidly progresses to acute liver failure if the infant is not delivered immediately. The only causal treatment for both diseases is immediate delivery. Expectant management between 24 + 0 and 33 + 6 weeks of gestation is recommended for HELLP syndrome, but only in cases where the mother can be stabilised and there is no evidence of foetal compromise. The maternal mortality rate for HELLP syndrome in developed countries is approximately 1%, while the rate for AFL is 1.8-18%. Perinatal mortality rates are 7-20% and 15-20%, respectively. While data on the long-term impact of AFL on the health of mother and child is still insufficient, HELLP syndrome is associated with an increased risk of developing cardiovascular, metabolic and neurological diseases in later life.
CRIS-Team Scopus Importer:2020-06-16
Keywords: acute fatty liver of pregnancy; differential diagnosis; HELLP syndrome; Swansea criteria; treatment and prognosis

Influence of Sonographic Fetal Weight Estimation Inaccuracies in Macrosomia on Perinatal Outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian; Mayr, Andreas; Schmid, Matthias; Staerk, Christian; Schild, Ralf; Beckmann, Matthias; Faschingbauer, Florian (Ultraschall in der Medizin, 2020)
Objective To evaluate the influence of inaccurate sonographic fetal weight estimation in macrosomia on the mode of delivery and neonatal outcome (NO). Methods In 14633 pregnancies between 2002 and 2016, this retrospective study evaluated the association between sonographic fetal weight estimation, true birth weight (BW), mode of delivery (primary cesarean section [pCS], secondary cesarean section, vaginal delivery, and operative vaginal delivery rates) and NO parameters (5-min Apgar <7, pH <7.1, neonatal intensive care unit [NICU] admission, shoulder dystocia). Singleton pregnancies >37+0 weeks with ultrasound-estimated fetal weight (EFW) within 7 days before delivery were included. The study population was divided into four groups: Group 1 (false-negative): EFW <4000g/BW ≥4000g; Group 2 (true-positive): EFW ≥4000g/BW ≥4000g; Group 3 (false-positive): EFW ≥4000g/BW <4000g; and Group 4 (true-negative): EFW <4000g/BW <4000g. Results As expected, the highest secondary cesarean section (sCS) rate was found in Group 2 (true-positive) (30.62%), compared with only 17.68% in Group 4 (true-negative). The sCS rate in the false-positive Group 3 was significantly higher (28.48%) in comparison with the false-negative Group 1 (21.22%; OR 1.48; 95% CI, 1.16 to 1.89; P=0.002). In comparison with the true-negative Group 4, univariate analyses showed significantly higher rates for sCS in all other groups: Odds ratio (OR) 2.06 for Group 2 (95% CI, 1.74 to 2.42; P<0.001), 1.85 for Group 3 (95% CI, 1.54 to 2.22, P <0.001), and 1.25 for Group 1 (95% CI, 1.05 to 1.49; P <0.01). No significant differences were found for NO between Groups 1 and 3 for the parameters 5-min Apgar <7 (P=0.75), pH <7.1 (P=0.28), or NICU admission (P=0.54). However, there was a significantly higher chance for shoulder dystocia in Group 1 compared with Group 3 (OR 4.58; 95% CI, 1.34 to 24.30; P=0.008). Conclusion Sonographic EFW inaccuracies in fetal macrosomia appear to have a greater impact on the mode of delivery than birth weight itself. Underestimation of fetal weight may be associated with a higher probability of shoulder dystocia.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cesarean section rate; fetal macrosomia; fetal weight estimation; perinatal outcome; sonography

Influence of sonographic fetal weight estimation in (suspected) fetal macrosomia on perinatal outcome - Pretscher, Jutta; Kehl, Sven; Stelzl, Patrick; Stumpfe, Florian; Mayr, A.; Schmid, M.; Staerk, C.; Schild, R. L.; Beckmann, Matthias; Faschingbauer, Florian (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Labour Induction with Misoprostol in German Obstetric Clinics: What Are the Facts on Such Use? - Kehl, Sven; Weiss, Christel; Rath, Werner; Schneider, Michael; Stumpfe, Florian; Faschingbauer, Florian; Beckmann, Matthias; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2021)
Subject While the synthetic prostaglandin E1 analogue misoprostol is the most effect labour induction agent, its use is off-label for the most part. For this reason, and in view of its potential adverse effects and varying approaches to its administration, the drug has recently once again become a focus of critical attention. The objective of this survey was thus to establish a record of labour induction with misoprostol in German clinics and determine the impact of the negative reporting on everyday obstetric practice.
CRIS-Team WoS Importer:2021-09-03

Maintenance tocolysis: a reappraisal of clinical evidence - Stelzl, Patrick; Kehl, Sven; Rath, Werner (Archives of Gynecology and Obstetrics, 2019)
Introduction: Maintenance tocolysis, mostly defined as the continuation of tocolytic treatment beyond 48 h, remains a matter of debate. There is no sufficient evidence from randomized controlled trials, that maintenance tocolysis is able to prolong pregnancy significantly and to reduce severe neonatal morbidity and mortality. Hence, it is not recommended in current guidelines. On the contrary, maintenance tocolysis is commonly used in clinical practice and subject of current clinical-scientific investigations. Tocolytics for maintenance treatment: None of the conventional tocolytics (beta-sympathomimetics, calcium-channel blockers, magnesium, cyclooxygenase inhibitors, and oxytocin receptor antagonists) have proven to be appropriate for maintenance treatment. Progesterone and 17-α-hydroxyprogesterone caproate have shown promising results in low-quality randomized trials, but not in high-quality studies. Discussion: Basically, the value of studies regarding maintenance tocolysis is limited by a considerable heterogeneity, its mostly low quality, significant differences in methodology as well as the inadequate statistical power due to the small number of women studied. So far, maintenance tocolysis is a case-by-case decision outweighing the benefits and harms of tocolytic treatment.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Efficacy; Maintenance tocolysis; Progesterone; Recommendations; Threatened preterm birth; Tocolytic agents

SARS-CoV-2 Infection in Pregnancy - a Review of the Current Literature and Possible Impact on Maternal and Neonatal Outcome - Stumpfe, Florian; Titzmann, Adriana; Schneider, Michael; Stelzl, Patrick; Kehl, Sven; Fasching, Peter; Beckmann, Matthias; Enßer, Armin (Geburtshilfe und Frauenheilkunde, 2020)
In December 2019, cases of pneumonia of unknown cause first started to appear in Wuhan in China; subsequently, a new coronavirus was soon identified as the cause of the illness, now known as Coronavirus Disease 2019 (COVID-19). Since then, infections have been confirmed worldwide in numerous countries, with the number of cases steadily rising. The aim of the present review is to provide an overview of the new severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2) and, in particular, to deduce from it potential risks and complications for pregnant patients. For this purpose, the available literature on cases of infection in pregnancy during the SARS epidemic of 2002/2003, the MERS (Middle East respiratory syndrome) epidemic ongoing since 2012, as well as recent publications on cases infected with SARS-CoV-2 in pregnancy are reviewed and reported. Based on the literature available at the moment, it can be assumed that the clinical course of COVID-19 disease may be complicated by pregnancy which could be associated with a higher mortality rate. It may also be assumed at the moment that transmission from mother to child in utero is unlikely. Breastfeeding is possible once infection has been excluded or the disease declared cured.
CRIS-Team Scopus Importer:2020-05-19
Keywords: 2019-nCoV; coronavirus; COVID-19; pregnancy; SARS-CoV-2